Clinical characteristics and risk factors associated with COVID-19 severity in patients with haematological malignancies in Italy: a retrospective, multicentre, cohort study. Issue 10 (October 2020) - Passamonti, Francesco; Cattaneo, Chiara; Arcaini, Luca; Bruna, Riccardo; Cavo, Michele; Merli, Francesco; Angelucci, Emanuele; Krampera, Mauro; Cairoli, Roberto; Della Porta, Matteo Giovanni; Fracchiolla, Nicola; Ladetto, Marco; et al.
Summary: Background: Several small studies on patients with COVID-19 and haematological malignancies are available showing a high mortality in this population. The Italian Hematology Alliance on COVID-19 aimed to collect data from adult patients with haematological malignancies who required hospitalisation for COVID-19. Methods: This multicentre, retrospective, cohort study included adult patients (aged ≥18 years) with diagnosis of a WHO-defined haematological malignancy admitted to 66 Italian hospitals between Feb 25 and May 18, 2020, with laboratory-confirmed and symptomatic COVID-19. Data cutoff for this analysis was June 22, 2020. The primary outcome was mortality and evaluation of potential predictive parameters of mortality. We calculated standardised mortality ratios between observed death in the study cohort and expected death by applying stratum-specific mortality rates of the Italian population with COVID-19 and an Italian cohort of 31 993 patients with haematological malignancies without COVID-19 (data up to March 1, 2019). Multivariable Cox proportional hazards model was used to identify factors associated with overall survival. This study is registered with ClinicalTrials.gov, NCT04352556, and the prospective part of the study is ongoing. Findings: We enrolled 536 patients with a median follow-up of 20 days (IQR 10–34) at data cutoff, 85 (16%) of whom were managed as outpatients. 440 (98%) of 451 hospitalised patients completed their hospital course (were either discharged alive or died). 198 (37%) of 536 patients died. When compared with the general Italian population with COVID-19, the standardised mortality ratio was 2·04 (95% CI 1·77–2·34) in our whole study cohort and 3·72 (2·86–4·64) in individuals younger than 70 years. When compared with the non-COVID-19 cohort with haematological malignancies, the standardised mortality ratio was 41·3 (38·1–44·9). Older age (hazard ratio 1·03, 95% CI 1·01–1·05); progressive disease status (2·10, 1·41–3·12); diagnosis of acute myeloid leukaemia (3·49, 1·56–7·81), indolent non-Hodgin lymphoma (2·19, 1·07–4·48), aggressive non-Hodgkin lymphoma (2·56, 1·34–4·89), or plasma cell neoplasms (2·48, 1·31–4·69), and severe or critical COVID-19 (4·08, 2·73–6·09) were associated with worse overall survival. Interpretation: This study adds to the evidence that patients with haematological malignancies have worse outcomes than both the general population with COVID-19 and patients with haematological malignancies without COVID-19. The high mortality among patients with haematological malignancies hospitalised with COVID-19 highlights the need for aggressive infection prevention strategies, at least until effective vaccination or treatment strategies are available. Funding: Associazione italiana contro le leucemie, linfomi e mieloma–Varese Onlus.